In-Season Repeated-Sprint Training in Hypoxia in International Field Hockey Players - James, Carl; Girard, Olivier (Frontiers in Sports and Active Living, 2020)
Repeated-sprint training in hypoxia (RSH) studies conducted “in-season” are scarce. This study investigated the effect of discontinuous, running-based RSH, on repeated-sprint treadmill performance in hypoxia in a team sport cohort, prior to international competition. Over a 6-week “in-season” period, 11 elite male players (Malaysia national team) completed eight multi-set RSH sessions on a non-motorized treadmill in a normobaric hypoxic chamber (FiO2 = 13.8%). Three testing sessions (Sessions 1, 5, and 8), involved three sets of 5 × 8-s sprints, with 52-s recovery between sprints and 4–5 min between sets. Training sessions (Sessions 2, 3, 4, 6, and 7) consisted of four to five sets of 4–5 × 8-s sprints. During testing sessions, maximum sprinting speed was recorded for each sprint with values averaged for each set. For each set, a peak speed and fatigue index were calculated. Data were compared using two-way repeated measures ANOVA (sessions × sets). Average speed per set increased between testing sessions (p = 0.001, ηp2 = 0.49), with higher values in Session 8 (25.1 ± 0.9 km.h−1, +4 ± 3%, p = 0.005), but not Session 5 (24.8 ± 1.0 km.h−1, +3 ± 3%, p = 0.405), vs. Session 1 (24.2 ± 1.5 km.h−1). Peak sprinting speed in each set also increased across testing sessions (p = 0.008, ηp2 = 0.382), with Session 8 (26.5 ± 1.1 km.h−1) higher than Session 5 (25.8 ± 1.0 km.h−1, +1 ± 4%, p = 0.06) and Session 1 (25.7 ± 1.5 km.h−1, +4 ± 4%, p = 0.034). Fatigue index differed between sessions (p = 0.04, ηp2 = 0.331, Session 1; −6.8 ± 4.8%, Session 5; −3.8 ± 2%, Session 8; −5.3 ± 2.6%). In international field hockey players, a 6-week in-season RSH program improved average and peak, repeated treadmill sprint speeds following eight, but not five sessions.